Rancangan Program Layanan Informasi untuk Peserta Didik yang Prokrastinasi Akademik di SMA N 1 Kecamatan Harau Kabupaten Lima Puluh Kota - Ovella Rahmadeni; Wira Solina; Joni Adison (Jurnal Neo Konseling, 2023)
This research is motivated by the presence of students spending free time for purposes that are not important, negligent in submitting assignments. This study aims to (1) describe academic procrastination, (2) design an information service program for students with academic procrastination. This type of research is descriptive quantitative. The population of this study was 168 students at SMA N 1 Harau. The sample in the study was 63 students taken using a purposive random sampling technique. The instruments used were questionnaires and for data analysis using interval scores and percentages with descriptive statistical techniques. The results of the study (1) students' academic procrastination are at high criteria. (2) the design of the information service program with time management, discipline material that the researchers designed for class XI SMA N 1 Harau District